Avaliação dos parâmetros do sêmen equino pré e pós-congelamento após separação dos espermatozoides com a utilização de lã de vidro - Silva, Rômulo Oliveira Fernandes da (2018)
The equine market is constantly growing, so the search for perfection in breeding and for better specimens intensifies and the freezing of semen helps in this process, being an important tool to preserve the genetics of animals considered superior within their breeds. In this study the sperm selection through glass wool, centrifugation and Sperm Filter® were evaluated on the motility, vigor, pH, concentration, morphology and membrane integrity of the frozen equine semen. The semen of five Brazilian ponies was diluted in an extender based on skim milk powder at a dilution of 1:1 and distributed in three groups: centrifugation (C), glass wool filtration + centrifugation (LC) and glass wool filtration + Sperm Filter® (LS). Four ejaculates of each pony were used. In the three groups evaluated after thawing there was no difference in the parameters of local motility, vigor and pH. The highest percentage of total motility (52.50% ± 7.16 and 48.50% ± 5.87) (P <0.01) and progressive motility (41.75% ± 7.30 and 38.25% ± 6.93) (P <0.01) was detected in groups C and LC, respectively. When evaluating sperm membrane integrity, superior results were detected in groups C and LC in relation to LS (43.25% ± 7.48, 42.35% ± 8.39 and 29.10% ± 12.31) (P <0.01). Sperm concentration was higher in group C (79.65 ± 27.15 x106sptz/mL) than LC and LS (43.97 ± 18.67 x106sptz/ml and 25.95 ± 21.84 x106sptz/mL) (P <0.01). In the computerized evaluation of sperm motility there was no difference between groups. When evaluating sperm morphology, we found fewer morphological defects after sperm selection in relation to immediate sperm morphology after collection. It suggested that, when preparing the semen for freezing, the use of centrifugation or glass wool + centrifugation is the protocol of choice.